Micro-Distribution of Land Snails in an Artificial Talus Slope - Raymond W. Neck (Hello World!, 1976)
An examination of an artificial talus slope in Alpine, Brewster Co., Texas, on December 17 1974 revealed a heterogeneous environment in relation to suitability of microhabitats for lanrl snails. This man-made talus slope formed an edge for a fill area which had been raised to a level plane from its natural slope, condition. Two types of rocks were used in the fill material (apparently at random as no intentional layering could be detected). Rocks included a light-colored aphanitic igneous rock and a hard fossiliferous Iimestone.